Development and Validation of an Affordable Calibration Method for Surface Plates - Garzón, Daniela; Galvis Arroyave, Jorge Luis; Plazas, David; Gil, Victor Hugo; Almanza, Ovidio; Galvis Arroyave, Jorge Luis (Universidad Nacional de Colombia, 2024)
The measurement and calibration of flat surfaces is highly relevant for precision engineering, length metrology, and optical systems. Hence, many National Metrology Institutes (NMIs) tend to offer calibration services in this regard. Typically, mechanical, electromechanical, and optical measuring techniques are applied, with uncertainties in the order of micrometers. However, these techniques necessitate expensive equipment that requires periodical calibration and maintenance, which not many laboratories can afford. This work presents the validation of an affordable and simple calibration technique for surface plates through the evaluation of metrological compatibility with a reference calibration method. A surface plate was calibrated with both methods under the same conditions to validate our proposal. The 2.9 µm uncertainty obtained with the new method demonstrates its reliability and usability for laboratories with surface plates up to 300 mm in length that have a grade AA to B flatness accuracy. Due to its low initial cost, reliability, and ease of implementation, the proposed calibration method can be recommended to all laboratories and industries that need to constantly verify their surface plates.